Parenting Patterns of Single Parents Father's Against Child Psychology - Hesti Meinawati; Ni Made Wiasti; Ni Luh Arjani (Udayana Journal of Social Sciences and Humanities, 2021)
This study uses a qualitative method. The collection technique used is using observation, interviews, and literature study. The research problems were analyzed using Structural-Functional Theory and Psychoanalytic Theory. The findings in this study are divided into two parts. First, the parenting pattern, the process of implementing the parenting style, the single parent Father takes care and educates the child by instilling values and norms, applying discipline, giving appreciation, providing religious education, meeting the physical needs of the child. In the process of parenting, there are obstacles and expectations of parents towards their children. Second, discussing the psychological implications for children, which can be seen in terms of children's moral behavior, children's personality and socialization, as well as children's play activities.